Интеграционные предпосылки энергосистем России и Украины: географический аспект - Атаев, З.А.; Ataev, Z.A. (Східноєвропейський національний університет імені Лесі Українки, 2013)
In this article the author considered spatial aspects of opportunities of integration of power industry of Russia and the Ukraine into the Euro-Asian power supply system. The sector review of spatial preconditions for branch integration is also carried out.
«Integration Preconditions of Power Supply Systems of Russia and the Ukraine: Geographical Aspect»
Атаев З.А., д.геог.н., доц., проф. кафедры энергетики, проректор по научной работе НОУ ВПО «Современный технический институт» (Россия, г. Рязань)
Keywords: Unified Energy System of Russia; integration of power production system; electric power system; electric energy sectors